Usefulness of milnacipran in treating phantom limb pain - Matsumoto Y (Dove Medical Press, 2012)
Yasuhide Nagoshi,1 Akira Watanabe,1 Saiko Inoue,1 Tomoki Kuroda,2 Mitsuo Nakamura,3 Yoshitake Matsumoto,4 Kenji Fukui31Department of Psychiatry (Psychosomatic Medicine), Kyoto First Red Cross Hospital, Kyoto, Japan; 2Gojouyama Hospital, Nara, Japan; 3Department of Psychiatry, Graduate School of Medical Science, Kyoto Prefectural University of Medicine, Kyoto, Japan; 4Matsumoto Clinic, Kyoto, JapanBackground: Amputation of an extremity often results in the sensation of a “phantom limb” where the patient feels that the limb that has been amputated is still present. This is frequently accompanied by “phantom limb pain”. We report here the use of milnacipran, a serotonin and norepinephrine reuptake inhibitor, to treat phantom limb pain after amputation of injured or diseased limbs in three patients.Methods and results: The severity of phantom pain before and during treatment was quantified using a visual analog scale. In one case, phantom limb pain responded partially to treatment with high doses of paroxetine, and then replacement with milnacipran further improved the pain relief and long-term full pain relief was achieved. In the two other cases, milnacipran was used as first-line treatment and phantom limb pain responded rapidly.Conclusion: These results suggest that milnacipran administration may be useful in phantom limb pain, possibly as a first-line treatment.Keywords: milnacipran, paroxetine, phantom limb pain, selective serotonin reuptake inhibitor (SSRI), serotonin and norepinephrine reuptake inhibitor (SNRI)